Implications for migrant workers rights in South Africa of ratification of the International Convention on the Protection of the Rights of all Migrant Workers and Members of the Families - Killander, Magnus (University of Pretoria, 2020)
Mini Dissertation (MPhil)--University of Pretoria, 2019.